2001
DOI: 10.1152/ajprenal.2001.280.2.f303
|View full text |Cite
|
Sign up to set email alerts
|

SGK integrates insulin and mineralocorticoid regulation of epithelial sodium transport

Abstract: The epithelial Na+ channel (ENaC) constitutes the rate-limiting step for Na+ transport across tight epithelia and is the principal target of hormonal regulation, particularly by insulin and mineralocorticoids. Recently, the serine-threonine kinase (SGK) was identified as a rapidly mineralocorticoid-responsive gene, the product of which stimulates ENaC-mediated Na+ transport. Like its close relative, protein kinase B (also called Akt), SGK's kinase activity is dependent on phosphatidylinositol 3-kinase (PI3K), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
209
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(236 citation statements)
references
References 45 publications
26
209
1
Order By: Relevance
“…Furthermore, there is evidence that aldosterone can affect insulin receptor mRNA levels, at least in cultured cells (36), and aldosterone levels have been correlated with insulin resistance (37). Finally, aldosterone induces the expression of the serum glucocorticoid-inducible kinase gene, whose expression level also responds to changes in glucose and insulin levels (38,39), suggesting yet another potential connection between aldosterone and glucose homeostasis. Alternatively, it is possible that arginine at residue 173 affects the activity of aldosterone synthase such that the rate of conversion of an intermediate to aldosterone is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that aldosterone can affect insulin receptor mRNA levels, at least in cultured cells (36), and aldosterone levels have been correlated with insulin resistance (37). Finally, aldosterone induces the expression of the serum glucocorticoid-inducible kinase gene, whose expression level also responds to changes in glucose and insulin levels (38,39), suggesting yet another potential connection between aldosterone and glucose homeostasis. Alternatively, it is possible that arginine at residue 173 affects the activity of aldosterone synthase such that the rate of conversion of an intermediate to aldosterone is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is interesting to note that SGK1 has been reported to physically interact with the Cterminal tails of ␣-ENaC and ␤-ENaC in vitro. However, there was no evidence that this association resulted in ENaC phosphorylation (25). Thus, as far as we know, specific phosphorylation of the serine residue 621 within the SGK consensus motif of ␣-ENaC has not yet been reported.…”
Section: Fig 10mentioning
confidence: 95%
“…This was initially demonstrated by co-expression experiments in Xenopus laevis oocyte (16,18,21,22) and more recently in cultured renal epithelial cells (23,24). SGK1 is thought to be an important molecular target that integrates multiple endocrine inputs regulating epithelial sodium transport (24,25). The recent development of SGK1 null mice has confirmed that the presence of SGK1 is important for the maintenance of sodium balance, since these animals develop pseudohypoaldosteronism when kept on a low sodium diet (26).…”
mentioning
confidence: 99%
“…Aldosterone-and insulin-mediated regulation of ENaC occurs through SGK1-mediated inhibition of Nedd4-2. 31, 101 Since these initial discoveries, a complex array of kinases has been shown to regulate ENaC directly and indirectly. For the purposes of this review, only recent discoveries are discussed.…”
Section: Intrinsic Factorsmentioning
confidence: 99%